Facilitation of Sclerotinia sclerotiorum infestation by aphid feeding behaviour is not affected by aphid resistance in oilseed rape - Zhong-Ping Hao; Zeng-Bei Feng; Lei Sheng; Wei-Xin Fei; Shu-Min Hou (Heliyon, 2024)
The relation between aphids and Sclerotinia stem rot (SSR) in oilseed rape is rarely examined because they are often studied alone. We have observed a significant correlation between the number of aphids and the occurrence of SSR in our field studies. Electropenetrography (EPG) was used to evaluate the effects of Brevicoryne brassicae (Linnaeus) on two oilseed rape cultivars while acquiring, vectoring and inoculating of Sclerotinia sclerotiorum Lib. (de Bary) ascospores. The results demonstrated that aphid feeding followed by the application of an ascospore suspension significantly increased S. sclerotiorum incidence. Aphids were capable of adhering to ascospores and carrying them to healthy plants, thereby causing diseases. The results of the EPG analysis indicated that aphid feeding behaviour was significantly altered in all leaf tissue levels following infection with S. sclerotiorum. Aphids initiated their first puncture significantly sooner than the control group, began probing mesophyll cells earlier, significantly increased the frequency of both short probes and intracellular punctures and had a significantly shorter pathway duration. On infected aphid-susceptible cultivars, aphids secreted more saliva but had reduced ingestion compared with aphids feeding on non-infected oilseed rape. In addition, ascospores can affect aphid feeding behaviour by adhering to aphids. Aphids carrying ascospores punctured cells earlier, with a significant increase in the frequency and duration of short probes and cell punctures, shortened pathway durations, increased salivation and reduced ingestion compared with aphids not carrying ascospores. On aphid-susceptible cultivars, aphids carrying ascospores delayed puncture onset, but on resistant cultivars, puncture onset was shortened. There is a correlation between aphids and S. sclerotiorum. The impact of S. sclerotiorum on aphid feeding behaviour is directional, favouring the spread of the fungus. This promotion does not appear to be altered by the aphid resistance of the cultivar.